Dynamic Simulation on Tool in Turning Process Using Depth of Cut Variance Using Harmonic Response System Analysis of Ansys - Agung Nugraha; Zulkarnain . (Universitas Sriwijaya, 2015)
High Speed Steel (HSS) is one of the most used material for making lathe tool, because of its ability to work under high rotation and friction condition without losing its mechanical properties significantly. on turning process, careful decision of machining parameters that matched its tool material ability for turning. In Simulation process, machining parameters which will be used in it had been researched by Pramod, Kumar, et al., (2014) with adjustments. machining parameters are feed rate at 0.24 mm/rev, spindle rotation at 1500 rpm, and main cutting angle are orthogonal cutting angle at (90). In this simulation, the writer using depth of cut variance of 1 mm, 1.5 mm, and 2 mm. purposes of using these variacuts are to find frequency and amplitude had ccured on lathe tool with different depth of cut